Gênese da estrutura agrária do Espírito Santo : estudo comparativo entre os domínios da pecuária no Extremo Norte e as áreas de pequenas propriedades no Centro-Sul - Bernardo Neto, Jaime (2012)
This work aims to contribute to the understanding of Espírito Santo rural land structure´s contrast, specially in what regards the large rural landed state genesis over the state´s extreme north, where the farming and cattle raising area´s percentage occupied by short rural landed state is low if compare to most of it´s territory reality. Due to the distance from the colonization irradiation´s cores and indigenous strong stand which lasted until the twentieth century´s beginning, among other factories, the colonization of this part of Espírito Santo only occur from the 1930´s and the 1940´s forward, being conditioned by a different structure from that which marked the colonization over most of it´s territory, which occur between the 19th century´s end and the 20th century beginning, in a context of large rural landed state crisis, due to the slavery abolishment, and commercial capital´s political hegemony, personified by the coffee dealer´s, to whom the spreading of uncapitalized short rural landed state owners which demanded intermediaries to accomplish their foreign marketing oriented commodities commercialization (notedly coffee) was beneficial, what resulted in favourable conditions for land appropriation in short glebes by peasant families, despite there has been a strong ethnic-racial selectivity benefiting foreign immigrants and their decedents. Nevertheless, this structures experiences deep changes from the 1930´s on which contributed to the entrance of more capitalized beings in rural production. From this moment on, the conditions demanded for rural land state to be used as a capital reserving fund turned out to be concrete, allowing it to be used for speculative means; there has also been changes in politics, as the industrial capital and rural oligarchy took over the hegemony; and It is verified the emergence of new economic activities in Espírito Santo´s rural space, such as the spreading of wood extracting and the fast increasing in bovine cattle raising. This factors´ synergy created a context of increasing adversity for peasants in general, who had to compete against characters who held more political and economic power, such as cattle farmers and enterprises, on the run for land appropriation over this last colonization frontier in Espirito Santos’s territory. It intensified the social exclusion in what regards access to land owning in such a way that in the 1970´s beginning the land owning concentration in this part of Espírito Santo was pretty much evident. Parallelly, from the middle twentieth century on it is verified changes in short landed state´s production over it’s territory which resulted in gradual forsake of self-consume production and/or local marketing production, both typical of peasant´s agriculture, due to a growing tendency to farm and cattle raising specialization, partially due to peasant´s ingress in capitalism marketing as a consequence of urbanization´s increasing, but also as a consequence of State´s politics aiming to increase peasant´s agriculture entrance in capital´s logic, which would consequently subordinate that. This increasing tendency turn out to confirm a territorial labour division in Espirito Santo´s agrarian space in which it´s Extremely North became deeply dependent of extensive bovine cattle raising, what was strongly adverse to short landed state owners due to the low value per area unit provided by this economic activity. Such changes came out to intensify this area´s land owning concentration in the last decades.